Unpacking a female language teacher’s identity transformations: a perspective of multiple I-positions - Xing, Huanling; Liu, Liyan; Jiang, Anne Li; Hunt, Neil (Frontiers in Psychology, 2024)
The narrative inquiry investigates the construction and evolution of a female Chinese language teacher's identity across her pre-service and in-service phases. Utilising data from interviews, class observation and written reflections, the research examines how internal and external aspects shape her identity development. It specifically explores the role of third positions, meta positions, and promoter positions drawing on the Dialogical Self Theory. The findings reaffirm that a teacher's identity is fluid and influenced by personal and professional factors. Over time, however, strong teaching beliefs and a growth mindset emerge as pivotal drivers for sustained and positive teacher development. The paper concludes by offering implications for pre-service teacher education and female teachers' continuing professional development.